Efficacy and Safety of Abiraterone Acetate and Enzalutamide for the Treatment of Metastatic Castration-Resistant Prostate Cancer: A Systematic Review and Meta-Analysis - Wei, ZhenHeng; Chen, ChuXin; Li, BoWen; Li, YongYue; Gu, Hong (Frontiers in Oncology, 2021)
Objective: The androgen receptor-targeting drugs abiraterone acetate and enzalutamide have shown positive results as treatments for metastatic castration-resistant prostate cancer (mCRPC). Therefore, a meta-analysis was conducted to compare the efficacy and safety of abiraterone acetate and enzalutamide in patients with mCRPC. Methods: We retrieved relevant articles from PubMed, Cochrane, and EMBASE published before December 31, 2020. Eleven articles were initially selected, and four phase III, double-blind, randomized controlled trials of abiraterone acetate and enzalutamide that involved 5199 patients with mCRPC were included. The end points were time to prostate-specific antigen progression (TTPP), according to the prostate-specific antigen working group criteria; overall survival (OS); and radiographic progression-free survival (rPFS). Results: Four randomized, controlled clinical trials involving 5199 patients were included in this study. The results of the meta-analysis showed that compared with the placebo alone, abiratone significantly improved the OS (HR=0.69, 95% CI: 0.60-0.8, P<0.00001), rPFS (HR=0.64, 95% CI: 0.57-0.71, P < 0.00001), and TTPP (HR=0.52, 95% CI: 0.45-0.59, P < 0.00001) in patients with mCRPC. Compared with the placebo, enzalutamide significantly improved the OS (HR=0.67, 95% CI: 0.59-0.75, P<0.00001), rPFS (HR=0.33, 95% CI: 0.29-0.37, P< 0.00001), and TTPP (HR=0.19, 95% CI: 0.17-0.22, P < 0.00001). An indirect comparison was performed to compare the efficacy of abiraterone and enzalutamide. The results showed that there was no significant difference between abiraterone and enzalutamide with regard to improving the OS of patients with mCRPC (HR=1.03, 95% CI: 0.854-1.242). Enzalutamide was superior to abiraterone with regard to improving rPFS in patients with mCRPC (HR=0.516, 95% CI: 0.438-0.608). With regard to improving TTPP, the efficacy of enzalutamide was better than that of abiraterone (HR=0.365, 95% CI: 0.303-0.441). Conclusions: Compared with the placebo, both abiraterone and enzalutamide significantly prolonged the OS, rPFS, and TTPP in patients with mCRPC. In addition, enzalutamide had better efficacy than abiraterone with regard to improving rPFS and TTPP but not OS, but the level of evidence was low. Therefore, a large direct comparison trial is needed to compare the efficacy of the two drugs.